The God Locus Of Control, Moral Disengagement and Ethical Perception Of Accounting Students: The Role Of Gender - Amelia Oktrivina; Lies Putriana; Murthada Sinuraya (Universitas Muhammadiyah Malang, 2024)
Purpose: The purpose of this study is to add to the understanding of ethical viewpoints in a corpus of accounting student literature, by using mediation and moderation models to examine the interaction between belief in divine control, moral detachment, gender, and ethical insight. Methodology/approach: A total of 324 students contributed to the study by completing a two-stage online survey. Findings: Using hierarchical moderated regression analysis, the findings underscore a substantive correlation between belief in divine control and moral detachment and ethical acumen. Practical implications: Moral detachment showed a negative correlation with ethical insight and served as an intermediary in the relationship between belief in divine control and ethical acumen. Originality/value: Furthermore, this study illustrates that gender acts as a condition variable affecting the correlation between belief in divine governance and moral disengagement, as well as the relationship between moral disengagement and ethical understanding, indicating that the dynamics of these relationships are affected by gender differences.